1998
DOI: 10.1117/1.601870
|View full text |Cite
|
Sign up to set email alerts
|

Interface roughness statistics of thin films from angle-resolved light scattering at three wavelengths

Abstract: The possibility of determining interface roughness and crosscorrelation statistics of the two interfaces of a thin film from angleresolved light scattering data at three wavelengths is investigated. It is shown that angle-resolved light scattering measurements at three wavelengths are not sufficient to determine the three power spectral density functions describing the thin film roughness. An attempt to combine reflectance and transmittance scattering to determine the roughness of a thin film on a transparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Rönnow [44] demonstrated (in an attempt to solve the inverse scattering problem) that a direct calculation of the PSD functions of double-layer coatings from ARS measurements performed at three illumination wavelengths results in impracticable high uncertainties.…”
Section: B Scattering Of Interference Coatingsmentioning
confidence: 99%
“…Rönnow [44] demonstrated (in an attempt to solve the inverse scattering problem) that a direct calculation of the PSD functions of double-layer coatings from ARS measurements performed at three illumination wavelengths results in impracticable high uncertainties.…”
Section: B Scattering Of Interference Coatingsmentioning
confidence: 99%
“…This form of merit function has been successfully applied to the fitting of angleresolved scattering measurements. 27 A downhill simplex algorithm 26,28 was applied to accomplish the merit function minimization. The result of this minimization is a parameter set P providing the best fit of the model to the experimental data.…”
Section: B Analysis Methodsmentioning
confidence: 99%
“…These studies have primarily relied on the presence or absence of interference features in the angular distribution of intensity that exist due to the interference of the fields scattered from each interface and exist only for optically thick films or multilayers. Angle-resolved light scattering at three different wavelengths has been employed to characterize a single dielectric layer, but it was found that not enough information is available to extract the roughness of each interface and the cross-correlation statistics [10].Recent work has demonstrated that the polarization of scattered light contains information that allows the source of scattering, be it surface roughness, subsurface defects, or particulate contamination, to be identified [11,12]. For example, measurements testing the consistency of the polarization with the matrix Q can be used to validate the use of Eqs.…”
mentioning
confidence: 99%
“…These studies have primarily relied on the presence or absence of interference features in the angular distribution of intensity that exist due to the interference of the fields scattered from each interface and exist only for optically thick films or multilayers. Angle-resolved light scattering at three different wavelengths has been employed to characterize a single dielectric layer, but it was found that not enough information is available to extract the roughness of each interface and the cross-correlation statistics [10].…”
mentioning
confidence: 99%